Realist evaluation of social outcomes in community care: the application of affordance theory to the Lindsay Leg Clubs. Issue 3 (27th May 2021) - Galazka, Anna Milena; Edwards, Tim; Harding, Keith
ABSTRACT: This study uses a scientific realist methodology to explain how social outcomes of community care interventions are produced, sustained and contextually dependent. We evaluate an organization dedicated to wound care and leg health known as the Lindsay Leg Club network, so far studied mostly from a phenomenological perspective, to demonstrate the generative role of places where Leg Clubs are located, with objects in their environment, and people who organize and run Leg Clubs, with their agency and intentionality. We theorize the explanatory role of these contextual features with the concept of affordances. Our approach shows that the phenomenological findings from community care evaluation are not unequivocal. Instead, researchers should recognize the nuanced nature of causality in social programmes, which requires a consideration of the links between community care interventions, how people respond to them and the conditions under which these responses are enacted.